Efektifitas Skrining Jaundice Berbasis Smartphone Mengurangi Prosedur Invasive pada Neonatus : Literature Review - Kusnul Hasanah; La Ode Abdul Rahman (Poltekkes Kemenkes Jakarta III, 2023)
Hyperbilirubinemia is the 5th leading cause of neonatal morbidity. Neonatal jaundice occurs in approximately 60% of newborns. To ensure proper management for preventing and treating jaundice in neonates, an effective screening method is required. The gold standard of bilirubin measurement with Total Serum Bilirubin (TSB), which involves invasive procedures, that can be painfull and carry the risk of infection. The purpose of this study to describe the implementation of smartphone-based methods in the assessment of detection and periodic monitoring of jaundice in neonates, as a non-invasive methods alternative, indirectly reducing invasive procedures. The study employed a literatur review method and presents a literature review of 11 selected journals. It was concluded that the smartphone application-based bilirubin assessment showed a significant correlation with TSB and TcB values. Smartphone-based applications can be considered as a non-invasive screening tool for bilirubin monitoring in neonates. The jaundice screening method based smatphone is expected to be applied, developed and made an algorithm for its implementation in hospital services or outside the hospital.